2019
DOI: 10.1248/cpb.c19-00163
|View full text |Cite
|
Sign up to set email alerts
|

<i>T</i><sub>2</sub> Relaxation Study to Evaluate the Crystalline State of Indomethacin Containing Solid Dispersions Using Time-Domain NMR

Abstract: The aim of this study was to demonstrate the usefulness of T 2 measurements conducted with a timedomain NMR (TD-NMR) for the characterization of active pharmaceutical ingredients (APIs) containing solid dosage forms. A solid dispersion (SD) and a physical mixture (PM) consisting of indomethacin (IMC) and polyvinylpyrrolidone (PVP) were prepared at different weight ratios as test samples, and then their T 2 relaxation curves were measured by TD-NMR. The T 2 relaxation curve of IMC was quite different from that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We have already demonstrated this analysis by testing two different binary blends consisting of IMC (a model API) and polyvinylpyrrolidone (PVP) (a model additive) 14) and consisting of amorphous and crystalline IMC. 13) Table 2 shows the free base contents estimated from the T 2 relaxation curves by using Eq. ( 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already demonstrated this analysis by testing two different binary blends consisting of IMC (a model API) and polyvinylpyrrolidone (PVP) (a model additive) 14) and consisting of amorphous and crystalline IMC. 13) Table 2 shows the free base contents estimated from the T 2 relaxation curves by using Eq. ( 5).…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the crystalline state of APIs by using TD-NMR. [13][14][15] In previous studies, we demonstrated that the T 1 and T 2 relaxation curves measured by TD-NMR could be applied to identify differences between amorphous and crystalline APIs: amorphous APIs showed shorter T 1 and longer T 2 than crystalline APIs because of the higher molecular mobility.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a technology that can evaluate the drug itself regardless of the functional group was desired. Therefore, we decided to measure the 1 H-NMR relaxation of the drug by NMR and report the dissolution profile of the drug, noting that the drug has 1 H and silica has almost no 1 H. The T 1 relaxation of solid drugs shows a larger difference between crystalline and amorphous than the T 2 relaxation 16) ; therefore, the T 1 relaxation was mainly measured and its behavior was compared between IBU-loaded T 1 (ms) T 1(short) (ms) T 1(long) (ms) P 1(short) (%) P SBA, IBU-loaded SYL, and IBU-loaded AER. First, we will discuss the NMR relaxation of IBU-loaded SBA that generated supersaturated solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we characterized the IBU-loaded SBA by its T 1 relaxation because the difference of T 1 values between amorphous and crystalline for solid samples is larger than that of T 2 relaxation. 16) Using this feature, the crystalline states of the drugs in SYL and AER could be distinguished as T 1(short) and T 1(long) values. It is also worth noting that a benchtop and low-field instrument was applied in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation